Justification of the effective design and operating parameters of the dosing and mixing device for the preparation of compound feed - Mammadov, Gabil; Saidov, Rasim; Hajiyev, Rovshan; Huseynova, Mehriban; Taghiyev, Urfan; Abdiyeva, Narmin; Imanova, Natavan; Allahverdiyeva, Gahira; Aliyev, Bahruz (Edelweiss Applied Science and Technology, 2025)
This article is about the study of the rational design and operational parameters of a dosing and mixing device in order to improve the accuracy of feeding concentrated feed to cows. The object of the research was the process of producing compound feed with dispersing force and the improved design and operational parameters of a screw-type liquid metering mixer. We investigated the operation of the developed experimental mixer in industrial settings (conducting pilot tests and obtaining results on the economic efficiency of its use). The design features of the metering mixer, design parameters for the operating mode, and practical recommendations for use, all of which were justified as a result of the research, are important for feed mills.